Association between glucose to lymphocyte ratio and prognosis in patients with solid tumors - Liu, Rongqiang; Shen, Yankun; Cui, Jiahui; Ma, Wangbin; Wang, Jianguo; Chen, Chen; Wang, Weixing (Frontiers in Immunology, 2024)
BackgroundGlucose-to-lymphocyte ratio (GLR) plays an important role in the prognosis of various tumors. The aim of this study was to comprehensively evaluate the prognostic value of GLR in solid tumors through the meta-analysis.MethodsA comprehensive search of eligible studies was performed by scrutinizing the Pubmed, Embase and Web of science databases until May 30, 2024. The pooled hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated to evaluate overall survival (OS), disease-free survival (DFS) and recurrence free survival (RFS).ResultsA total of 22 studies from 14 articles involving 9472 patients were included in the study. The pooled analysis showed that cancer patients with high GLR was significantly associated with unfavorable OS (HR:1.48,95% CI:1.34-1.63) and DFS/RFS (HR:2.20,95% CI:1.66-2.92). Subgroup analysis further showed that high GLR had better predictive value in liver cancer (HR:2.66, 95%CI:1.80-3.93), breast cancer (HR:2.13, 95%CI:1.10-4.13) and pancreatic cancer (HR:1.92, 95%CI:1.30-2.84).ConclusionsGLR can be used as an effective prognostic marker in patients with solid tumors.